THERMAL CONDUCTIVITY OF BIOMORPHIC POROUS SIC BASED CERAMICS - Popovska, Nadejda; Alkhateeb, Emad; Kugler, Tanja; Fröba, Andreas Paul; Leipertz, Alfred (14th International Heat Transfer Conference, 2010)
Biomorphic porous SiC composite ceramics were produced by chemical vapor infiltration and reaction (CVI-R) technique using paper preforms as template. The thermal conductivity of four samples with different composition and microstructure was investigated: a) C-template b) C-SiC, c) C-SiC-Si3N4 and d) SiC coated with a thin layer of TiO2. The SiC-Si3N4 composite ceramic showed enhanced oxidation resistance compared to single phase SiC. However; a key property for the application of these materials at high temperatures is their thermal conductivity. The later was determined experimentally at defined temperatures in the range 298-373K with a laser flash apparatus. It was found that the thermal conductivity of the porous ceramic composites increases in the following order: C-template < C-SiC < C-SiC-Si3N4 < SiC-TiO2. The results were interpreted in regard to the porosity and the microstructure of the ceramics.
Keywords: united

Thermal conductivity of porous SiC composite ceramics derived from paper precursor - Popovska, Nadejda; Alkhateeb, Emad; Fröba, Andreas Paul; Leipertz, Alfred (Ceramics International, 2010)
Biomorphic porous SiC composite ceramics were produced by chemical vapor infiltration and reaction (CVI-R) technique using paper precursor as template. The thermal conductivity of four samples with different composition and microstructure was investigated: (a) C-template, (b) C-SiC, (c) C-SiC-Si3N4 and (d) SiC coated with a thin layer of TiO2. The SiC-Si3N4 composite ceramic showed enhanced oxidation resistance compared to single phase SiC. However, a key property for the application of these materials at high temperatures is their thermal conductivity. The later was determined experimentally at defined temperatures in the range 293-373 K with a laser flash apparatus. It was found that the thermal conductivity of the porous ceramic composites increases in the following order: C-template < C-SiC < C-SiC-Si3N4 < SiC-TiO2. The results were interpreted in regard to the porosity and the microstructure of the ceramics. (C) 2010 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Porosity; Thermal conductivity; Thermal applications; Biomorphic SiC ceramics